2022
DOI: 10.3762/bjnano.13.40
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanostructures for fluorescence and Raman signal enhancement: a review

Abstract: Since the initial discovery of surface-enhanced Raman scattering (SERS) and surface-enhanced fluorescence (SEF), these techniques have shown huge potential for applications in biomedicine, biotechnology, and optical sensors. Both methods rely on the high electromagnetic fields created at locations on the surface of plasmonic metal nanoparticles, depending on the geometry of the nanoparticles, their surface features, and the specific location of analyte molecules. Lately, ZnO-based nanostructures have been expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 125 publications
2
6
0
Order By: Relevance
“…2(a) that the increase in temperature caused a gradual reduction in fluorescence intensity, which can be attributed to the presence of thermal energy inducing electronic vibrations that release non-radiative energy. 23 Furthermore, time-dependent fluorescence intensity was studied at 5 minute intervals over 30 minutes and it was found that the intensity remained constant over time, with the peak intensity consistent with that shown in Fig. 2(b).…”
Section: Resultssupporting
confidence: 66%
“…2(a) that the increase in temperature caused a gradual reduction in fluorescence intensity, which can be attributed to the presence of thermal energy inducing electronic vibrations that release non-radiative energy. 23 Furthermore, time-dependent fluorescence intensity was studied at 5 minute intervals over 30 minutes and it was found that the intensity remained constant over time, with the peak intensity consistent with that shown in Fig. 2(b).…”
Section: Resultssupporting
confidence: 66%
“…We can see from Figure 2(a) that the increase in temperature caused a gradual reduction in fluorescent intensity, which can be attributed to the presence of thermal energy inducing electronic vibrations that result in the release of non-radiative energy. 15 Furthermore, time-dependent fluorescence intensity was studied at 5-minute intervals over 30 minutes and found that the intensity remained constant over time, with the peak intensity consistent with that shown in Figure 2(b). Our investigation on the effects of prolonged light exposure and temperature indicates that the CNPs synthesized exhibit good photostability and thermal stability with a slight decrement in intensity as the temperature rises.…”
Section: Optical Properties Of Cnpssupporting
confidence: 60%
“…One of the challenges in using fluorescence-imaging-based quantification is the low fluorescence emission of organic dyes which resulted in low sensitivity and small dynamic range, as previously described. ZnO nanostructures are well-known for their ability to amplify fluorescence at their surface, making them a promising choice as enhancers in fluorescence-based sensors . This property is due to the evanescent electric field that is generated at the surface of the nanostructure, which enhances the excitation energy of organic dyes across a broad spectrum of visible light.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO nanostructures are well-known for their ability to amplify fluorescence at their surface, making them a promising choice as enhancers in fluorescence-based sensors. 44 This property is due to the evanescent electric field that is generated at the surface of the nanostructure, which enhances the excitation energy of organic dyes across a broad spectrum of visible light. FAM conjugated aptamer−cDNA duplex probes were utilized to verify the effective immobilization of the aptamer−cDNA duplex on the MBs-ZnO NRs (Figure S6).…”
Section: Biosensing Platform Based Onmentioning
confidence: 99%